Integrated analysis of halogenated organic pollutants in sub-millilitre volumes of venous and umbilical cord blood sera - Grimalt, Joan O.; Howsam, Mike; Carrizo, Daniel; Otero, Raquel; Marchi, Mary Rosa Rodrigues de [UNESP]; Vizcaino, Esther (Springer Nature, 2010)
A rapid, robust and economical method for the analysis of persistent halogenated organic compounds in small volumes of human serum and umbilical cord blood is described. The pollutants studied cover a broad range of molecules of contemporary epidemiological and legislative concern, including polychlorobiphenyls (PCBs), polychlorobenzenes (CBs), hexachlorocyclohexanes (HCHs), DDTs, polychlorostyrenes (PCSs) and polybromodiphenyl ethers (PBDEs). Extraction and clean-up with n-hexane and concentrated sulphuric acid was followed with analysis by gas chromatography coupled to electron capture (GC-ECD) and GC coupled to negative ion chemical ionisation mass spectrometry (GC-NICI-MS). The advantages of this method rest in the broad range of analytes and its simplicity and robustness, while the use of concentrated sulphuric acid extraction/clean-up destroys viruses that may be present in the samples. Small volumes of reference serum between 50 and 1000 μL were extracted and the limits of detection/quantification and repeatability were determined. Recoveries of spiked compounds for the extraction of small volumes (≥300 μL) of the spiked reference serum were between 90% and 120%. The coefficients of variation of repeatability ranged from 0.1-14%, depending on the compound. Samples of 4-year-old serum and umbilical cord blood (n = 73 and 40, respectively) from a population inhabiting a village near a chloro-alkali plant were screened for the above-mentioned halogenated pollutants using this method and the results are briefly described. © 2010 Springer-Verlag.
Keywords: Blood serum; Endocrine disruptors; GC-ECD; GC-MS; Pesticides; Trace halogenated organic compounds; Umbilical cord serum; Venous serum; Endocrine disruptor; Halogenated organic compounds; Umbilical cords; Alkalinity; Blood; Electrochemical sensors; Electrochromic devices; Ethers; Gas chromatography; Halogenation; Hexane; Mass spectrometry; Polychlorinated biphenyls; Reduction; Sulfuric acid; Viruses; Organic pollutants; halogenated hydrocarbon; blood; chemistry; electrospray mass spectrometry; evaluation; female; fetus blood; gas chromatography; human; male; methodology; pollutant; preschool child; serum; statistical parameters; Child, Preschool; Chromatography, Gas; Environmental Pollutants; Female; Fetal Blood; Humans; Hydrocarbons, Halogenated; Limit of Detection; Male; Serum; Spectrometry, Mass, Electrospray Ionization